أثر الذكاءات المتعددة على تحسين نتائج تعلم اللغة العربية في المدرسة المتوسطة الإسلامية: The Effect of Multiple Intelligences on Improving Arabic Language Learning Outcomes at Islamic Junior High Schools - Adifiah, Putri; Kamal, Helmi (Al Ibrah: Journal of Arabic Language Education, 2024)
This study discusses the application of Multiple Intelligences-based learning to enhance the active participation of eighth-grade students at SMPIT Al-Hafizh, Palopo City, in Arabic language learning. The research aims to (1) identify forms of Multiple Intelligences-based learning that effectively increase student engagement and (2) evaluate how this approach can foster active learning in the classroom. Employing a Classroom Action Research (CAR) methodology, the study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The findings indicate a significant improvement in student activity and engagement. In the first cycle, 8 out of 10 students (80%) achieved the learning objectives, while 2 students (20%) did not. In the second cycle, all 10 students (100%) successfully reached the objectives, marking a 20% improvement. The results highlight that Multiple Intelligences-based learning creates an interactive and engaging environment, allowing students to explore various strengths and styles of learning. The study recommends implementing this approach to address diverse student needs and enhance active learning. It also emphasizes the importance of incorporating creative and adaptive teaching strategies to maximize student motivation and outcomes in Arabic language instruction. يتناول هذا البحث تطبيق التعلم القائم على الذكاء المتعدد لزيادة نشاط تعلم اللغة العربية لدى طلاب الصف الثامن في المدرسة المتوسطة الإسلامية المتكاملة الحافظ فالوفو. يهدف البحث إلى (1) تحديد أشكال التعلم القائم على الذكاء المتعدد التي يمكن أن تزيد من نشاط الطلاب، و(2) تقييم كيفية تطبيق هذا النهج لتعزيز النشاط التعليمي داخل الفصل الدراسي. اعتمد البحث على منهج البحث الإجرائي الصفي (CAR) الذي تم تنفيذه في دورتين شملتا مراحل التخطيط، والتنفيذ، والملاحظة، والتقييم. أظهرت النتائج تحسناً ملحوظاً في نشاط الطلاب. ففي الدورة الأولى، أتم 8 من أصل 10 طلاب البرنامج بنسبة (80%)، بينما لم يكمل طالبان بنسبة (20%). أما في الدورة الثانية، فقد أتم جميع الطلاب العشرة البرنامج بنسبة (100%)، مما يشير إلى زيادة قدرها (20%). تؤكد هذه النتائج فعالية التعلم القائم على الذكاء المتعدد في خلق بيئة تعليمية تفاعلية تعزز من مشاركة الطلاب. يوصي البحث بتطبيق هذا النهج لتلبية احتياجات الطلاب المختلفة وتحفيزهم على التعلم النشط، مع التأكيد على أهمية استخدام استراتيجيات تدريس مبتكرة لتعزيز نتائج تعلم اللغة العربية.